Performance analysis of hybrid cryptosystem - A technique for better security using blowfish and RSA - Timilsina, Suresh; Gautam, Sarmila (Journal of Innovations in Engineering Education, 2019)
Security is the most concerned topic in this today’s world of Information and Communication Technology. Single layer security can be breached easily so hybrid cryptographic system has been introduced. Hybrid system can be made by combining two or more algorithms of similar or dissimilar types. Here, combing of Blowfish algorithm along with RSA algorithm is performed. After combination their performance analysis is done based on five parameters namely Throughput, Encryption time, Decryption time, Total Execution time and Plain text size to cipher text size ratio with different key size of Blowfish algorithm ranging from 32 bit-448 bit. Among these 5 different hybrid cryptosystem we found that the Blowfish RSA system with key size 448 bit has better performance than all other bit size.